PELAKSANAAN KEBIJAKAN OTONOMI DAERAH DALAM BIDANG PENDIDIKAN - durotun; Anis Fauzi; Abdul Muin (Qalam : Jurnal Ilmu Kependidikan, 2023)
The relationship between regional autonomy policy and autonomy in the field of education is very significant. The autonomy granted to regions in the field of education provides freedom for regions to make changes that ensure excellence in education. The purpose of this study was to comprehensively describe the implementation of regional autonomy in the field of education. The research method used is literature review by collecting information from sources, reading, recording, and managing material critically and analytically related to research. In this regard, educational autonomy must certainly receive significant support from a number of groups, including all aspects that include in the management of institutions to help learners develop the abilities, knowledge, and attitudes necessary in order to contribute to society at large. Some of the elements that hinder the implementation of a policy, namely interpretations that cause disputes between individuals due to lack of support for human resources and non-human resources and community understanding are not adequate in the tiered socialization system carried out by the Education Office.